PENEGAKAN HUKUM TINGKAT PENYIDIKAN TERHADAP PELAKU TINDAKAN EIGENRICHTING (MAIN HAKIM SENDIRI) DI KOTA PONTIANAK - NIM. A1011201226, MANDA TRI FITRIANI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract In the implementation of the law does not always match what should be (Das Sollen) and what is actually (Das Sein). This can be seen from the remaining action of judge. To that end, given that Indonesia is a legal state where everything should be legally, then against this deviant action shall be enforced. The problem in this study is